Reciprocity and Migration: The Interface between Religions - Mekonnen , Endale S. (African Human Mobility Review, 2021)
Much has been said on migration in current scholarly discourses within and multi-disciplinary debates. But no sufficient input has been generated towards the discourse from a religious perspective, albeit extremely needed insofar as people migrate with their religion. This inquiry examines the interplay between reciprocity and migration from a religious perspective using primary and secondary source analysis. It also suggests that cultivating religions’ cultural ideology of positive, responsible and balanced reciprocity in a societal relationship based on mutual benefits mediates a healthy co-existence between the native and the migrants despite their invariably differing and competing religions. Such reciprocity could be spawned through the sacred texts of religions that espouse either general or positive balanced reciprocity. In the course of the analysis, the work brings the Golden Rule into focus as the best candidate for a test case.